Antimicrobial, Antioxidant and Cytotoxic Activity of Silver Nanoparticles Synthesized by Leaf Extract of Erythrina suberosa (Roxb.) - Mohanta, Yugal K.; Panda, Sujogya K.; Jayabalan, Rasu; Sharma, Nanaocha; Bastia, Akshaya K.; Mohanta, Tapan K. (Frontiers in Molecular Biosciences, 2017)
In this experiment, biosynthesized silver nanoparticles were synthesized using aqueous leaf extract of Erythrina suberosa (Roxb.).The biosynthesis of silver nanoparticle was monitored using ultraviolet-visible spectroscopy. The effect of the phytoconstituents present in E. suberusa, on formation of stable silver nanoparticles was analyzed by fourier-transform infrared spectroscopy. The size, charge and polydispersity nature of silver nanoparticles were studied using dynamic light scattering spectroscopy. The morphology of the nanoparticles was determined by scanning electron microscopy. The result indicates that the glycosides, flavonoids and phenolic compounds present in the plant extract played a major role in the biosynthesis of silver nanoparticles. The antimicrobial activities of nanoparticles were evaluated against different pathogenic bacterium and fungi. The antioxidant property was studied by radical scavenging (DPPH) assay and cytotoxic activity was evaluated against A-431 osteosarcoma cell line by MTT assay. The characteristics of the synthesized silver nanoparticles suggest their application as a potential antimicrobial and anticancer agent.